EU Climate Mitigation Policy - Chen, Jiaqian (Departmental Papers; Departmental Paper ;, 2020)
This paper aims to contribute to the debate on the choice of policies to reach the more ambitious 2030 emission reduction goals currently under consideration. It provides an analysis of the macroeconomic and distributional impacts of different options to scale up the mitigation effort, and proposes enhancements to the existing EU policies. A key finding is that a well-designed package, consisting of more extensive carbon pricing across EU countries and sectors, combined with cuts in distortionary taxes and targeted green investment support, would allow the EU to reach the emission goals with practically no effects on aggregate income. To enhance the social and political acceptance of climate policies, part of the revenue from carbon pricing should be used to compensate the most vulnerable households and to support the transition of workers to greener jobs. A carbon border adjustment mechanism could complement the package to avoid an increase in emissions outside the EU due to higher carbon prices in the EU ('carbon leakage'). From a risk-reward perspective, the benefits of reducing the risk of extreme life-threatening climate events and the health benefits from lower air pollution clearly outweigh the costs of mitigation policies.